Preemergence herbicide premixes reduce the risk of soil residual weed control failure in corn - Silva, Tatiane Severo; Arneson, Nicholas John; DeWerff, Ryan P.; Smith, Daniel H; Silva, Daniel Valadão; Werle, Rodrigo (Weed technology, 2023)
Widespread occurrence of herbicide-resistant weeds and more variable weather conditions across the United States has made weed control in many crops more challenging. Preemergence (PRE) herbicides with soil residual activity have resurged as the foundation for early season weed control in many crops. Field experiments were conducted in Janesville and Lancaster, Wisconsin, in 2021 and 2022 (4 site-years) to evaluate the weed control efficacy of solo (single site of action [SOA]) and premix (two or more SOAs) PRE herbicides in conventional tillage corn. Treatments consisted of 18 PRE herbicides plus a nontreated check. At the Janesville-2021 site, S-metolachlor + bicyclopyrone + mesotrione, atrazine + S-metolachlor + bicyclopyrone + mesotrione, and clopyralid + acetochlor + mesotrione provided >72% giant ragweed control. At the Janesville-2022 site, none of the PRE herbicides evaluated provided >70% giant ragweed control due to the high giant ragweed density and the lack of timely rainfall. At the Lancaster-2021 site, atrazine, dicamba, and flumetsulam + clopyralid provided <45% waterhemp control, but the remaining treatments provided >90% control. At the Lancaster-2022 site, the efficacy of some PRE herbicides was reduced due to the high waterhemp density; however, most herbicides provided >75% control. At the Lancaster-2021 and Lancaster-2022 sites, only dicamba and S-metolachlor did not provide >75% common lambsquarters control. Group 15 PRE herbicides provided >75% control of giant foxtail. Across weed species, PRE herbicides with two (78%) and three (81%) SOAs provided greater weed control than PRE herbicides with a single SOA (68%), indicating that at least two SOA herbicides applied PRE result in better early season weed control. The efficacy of the PRE herbicide treatments evaluated herein varied according to the soil seedbank weed community composition and environmental conditions (i.e., rainfall following application), but the premixes were a more reliable option to improve early season weed control in conventional tillage corn. Nomenclature: Common lambsquarters; Chenopodium album L.; corn; Zea mays L.; giant foxtail; Setaria faberi Herrm.; giant ragweed; Ambrosia trifida L.; waterhemp; Amaranthus tuberculatus [Moq.] J.D. Sauer